Working With a Unionized Faculty - John R Hamilton Jr (Academic Chairpersons Conference Proceedings, 2018)
Newly appointed supervisors are often concerned when they must oversee the work of employees who are members of a union. This workshop provides some basic information about unions and tips to being a good supervisor or manager in a union environment. The information is appropriate for Chairpersons and Deans.
Keywords: Unions; supervision; due process; accountability; documentation; and counseling